2001
DOI: 10.1128/aem.67.8.3476-3480.2001
|View full text |Cite
|
Sign up to set email alerts
|

Bile Salt Hydrolase Activity and Resistance to Toxicity of Conjugated Bile Salts Are Unrelated Properties in Lactobacilli

Abstract: Bacteria of numerous species isolated from the human gastrointestinal tract express bile salt hydrolase (BSH) activity. How this activity contributes to functions of the microorganisms in the gastrointestinal tract is not known. We tested the hypothesis that a BSH protects the cells that produce it from the toxicity of conjugated bile salts. Forty-nine strains of numerous Lactobacillus spp. were assayed to determine their capacities to express BSH activities (taurodeoxycholic acid [TDCA] hydrolase and taurocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
103
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(122 citation statements)
references
References 20 publications
14
103
2
3
Order By: Relevance
“…It has been suggested that the major effect of bile acids would be the disaggregation of the lipid bilayer structure of the cell membrane. The tolerance to bile salts was initially associated with the presence of bile salt hydrolase activity (Moser and Savage, 2001;Taranto et al, 2006).…”
Section: Characterization Of Primary Probiotic Properties Of Ent Faementioning
confidence: 99%
“…It has been suggested that the major effect of bile acids would be the disaggregation of the lipid bilayer structure of the cell membrane. The tolerance to bile salts was initially associated with the presence of bile salt hydrolase activity (Moser and Savage, 2001;Taranto et al, 2006).…”
Section: Characterization Of Primary Probiotic Properties Of Ent Faementioning
confidence: 99%
“…Table 1 shows that some strains were able to grow in the presence of conjugated bile salts while they were not able to deconjugate them. This fact can be attributed to the ability of isolates to express bile salt hydrolase (BSH) activity which is not related to their ability to resist the toxicity of conjugated bile salts [Moser & Savage, 2001]. …”
Section: Bile Salts Deconjugationmentioning
confidence: 99%
“…Otro mecanismo por el cual la levadura es resistente a altas concentraciones de sales biliares, se centra en la acumulación de polioles y glicerol, como mecanismo para regular la presión osmótica de la célula. Moser y Savage (18), indicaron que las especies de levaduras que toleran sales biliares contribuyen a la función de los microorganismos en el tracto gastrointestinal (19); lo cual deberá ser demostrado posteriormente con nuestras sepas.…”
Section: Discussionunclassified